In vitro antifungal properties of Pistacia atlantica and olive extracts on different fungal species - Zahra Shialy; Majid Zarrin; Batool Sadeghi-Nejad; S Yusef Naanaie (Mazandaran University of Medical Sciences, 2015)
Background and Purpose: Pistacia atlantica, which belongs to the Anacardiaceae family, grows in the Zagrossian region of Iran. The aim of this study was to evaluate the antifungal properties of Pistacia atlantica and olive leaf extracts against different fungal species. Materials and Methods: In this study, we assessed the activities of olive leaf extracts and Pistacia atlantica leaf and fruit extracts against Candida species, including C. albicans, C. glabrata, C. tropicalis, and C. krusei. In addition, antifungal activities against three filamentous species, i.e., Aspergillus niger, Aspergillus flavus, and Aspergillus fumigates, were assessed, using the agar-well diffusion method. Results: The minimal inhibitory concentrations (MICs) values of fruit and leaf extracts from Pistacia atlantica ranged 6.25-12.5 mg ml-1 and 6.25-25 mg ml-1 against the tested Candida and Aspergillus species, respectively. The olive leaf extracts showed no activity against Candida species or Aspergillus flavus, while they exhibited antifungal potency against Aspergillus niger and Aspergillus fumigatus (MIC: 12.5-25 mg/ml). The MICs of the mixture of selected extracts ranged from 6.25 to 25 mg/ml. Conclusion: Based on the results, the ethanolic extracts of the selected plants exhibited antifungal potency against the tested fungi and could be used as natural antifungal agents.